What a Catch: Safety Intervention to Reframe Newborn Falls and Drops. Issue 3 (May 2021) - Knipper, Nora P.; DiCioccio, Heather Condo; Albert, Nancy M.
Abstract: Background: Parental fatigue rates after childbirth are high and may be associated with newborn drops that cause injury. Newborn drops and near-misses are potentially underreported due to parental embarrassment, shame, fear of reprisal, or guilt. Although newborn drops are rare, the leaders of mother–baby units need to enhance transparency of risk to assure a culture of safety. Purpose: To describe components and outcomes of the What A Catch program, aimed at preventing newborn drops and addressing near-misses. Methods: The What A Catch program was implemented in two hospital mother–baby units. The five components of the program included maintaining a respite nursery, using visual management, positively framing situational communication and actions after a near-miss, safe and appropriate staffing, and celebrating and transparently displaying program successes. Data were collected on near-miss event rates and caregivers and families provided postevent comments. Results: The perinatal team embraced the program at both sites. Of 9, 578 live births over 1 year, 202 near-misses or good catches were documented. Program leaders revise display the board multiple times per week. Clinical Implications: Replication of this program is needed to determine if all five components are necessary to optimize a culture of safety. Future research may determine the scope of risk factors associated with newborn drops and near-misses, so that anticipated risk factors can be mitigated. Abstract : Newborn falls or drops in the hospital are serious safety events and can result in significant injuries to the baby. Parental guilt is a common consequence. Nurses implemented a newborn falls prevention program in two mother-baby units within one health care system. They report on aspects of the program, successes, and suggestions for application in other birthing hospitals.